2021
DOI: 10.31989/ffhd.v11i3.775
|View full text |Cite
|
Sign up to set email alerts
|

The green tea polyphenol EGCG is differentially associated with telomeric regulation in normal human fibroblasts versus cancer cells

Abstract: Introduction: Topical investigations have demonstrated that oxidative stress and inflammation play key roles in biological aging and determine incidence and course of age-related diseases. Lifestyle and environmental factors hugely impact epigenetic regulation and DNA stability with telomere attrition and epigenetic instability providing a potential record of the cumulative burden of endogenous and exogenous oxidative noxae. Certain physiologically active plant components exhibit antioxidative activities affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…uric acid, glutathione), while others are ingested through the diet. Exogenous antioxidants, including polyphenols and their derivatives, are well described in the scientific literature [23]. The number and position of hydroxyl groups in the molecule determine their antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…uric acid, glutathione), while others are ingested through the diet. Exogenous antioxidants, including polyphenols and their derivatives, are well described in the scientific literature [23]. The number and position of hydroxyl groups in the molecule determine their antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, relatively longer telomeres along with increased methylation were observed in fibroblasts after treatment with EGCG. Also, antioxidant activity was reported at 20 and 200 µM [ 50 ]. Furthermore, it was detected that EGCG can bargain some protection against UV-induced DNA damage in cell cultures and human peripheral blood samples [ 51 ].…”
Section: Egcg and Cancer Hallmarksmentioning
confidence: 99%
“…The effects of EGCG on telomerase activity were observed in several cancer models. It was reported that 20 and 200 µM of EGCG caused telomere shortening and decreased telomerase activity in Caco-2 cells [ 50 ]. Moreover, in glioblastoma, EGCG suppressed the growth of U251 cells through telomerase inhibition [ 106 ].…”
Section: Egcg and Cancer Hallmarksmentioning
confidence: 99%
“…Methylation of c-Myc is considered an indirect mechanism used to regulate telomerase through hTERT. In fact, it has been observed that c-Myc methylation is significantly higher in some tumor cell lines after treatment with EGCG [ 193 ]. The methylation status of hTERT was, in some cancer cell lines such as Caco-2 cells, little affected by EGCG treatment [ 193 ].…”
Section: Potential (Poly)phenol Targets In Senescent and Cancer Cellsmentioning
confidence: 99%
“…In fact, it has been observed that c-Myc methylation is significantly higher in some tumor cell lines after treatment with EGCG [ 193 ]. The methylation status of hTERT was, in some cancer cell lines such as Caco-2 cells, little affected by EGCG treatment [ 193 ]. Conversely, in other tumor cell lines, such as HeLa cells (cervical tumor cell line) a significant decrease in telomere length and decreased telomerase activity was observed after treatment with EGCG [ 182 ].…”
Section: Potential (Poly)phenol Targets In Senescent and Cancer Cellsmentioning
confidence: 99%